Women's participation in academic conferences in Israel. Issue 4 (3rd July 2016) - Eden, Devorah
ABSTRACT: This article examines the participation of women in academic conferences in Israel, a country in which women are under-represented in academia vertically and horizontally. Data were retrieved from announcements of academic conferences in Israel, for one academic year, covering 56 conferences that attracted 997 participations. Participation was measured according to a three-level vertical hierarchy and a three-level horizontal divide that was based on academic discipline. Statistical z -tests and χ 2 tests were conducted to compare the proportions of male and female participation. Findings show that male participation in conferences was three times that of women. It was also found that the conferences reflected the social agenda in Israel. It is suggested that women are subjected to two forms of gender marginality, one stemming from the gendered division of labour and the other from the characteristics of the academic conferences that reflect the masculine military social agenda in Israel.